Criteria for prioritizing selection of Mexican maize landrace accessions for conservation in situ or ex situ based on phylogenetic analysis - Martínez, Octavio; Ojeda, Adriana Ceniceros; Hayano-Kanashiro, Corina; Reyes Valdés, M. Humberto; Hernández, José Luis Pons; Simpson, June (Frontiers in Ecology and Evolution, 2023)
A combination of factors including migration, climate change and the encroachment of growing cities are associated with the extinction of species and a reduction in biodiversity. In Mexico maize landraces are an important source of germplasm that could be invaluable for future breeding programs in response a changing environment. Efforts to develop conservation strategies are hampered by the costs of housing and maintaining large germplasm collections. Effective criteria are therefore needed to identify rare genotypes that are in danger of being lost and to define minimal cost -effective core collections. With this aim a large-scale genotyping analysis of Mexican maize landraces was carried out to determine relationships at the genotype level and identify rare germplasm. Using this methodology, a core subset of 56 accessions from a total number of 1338 carrying all 333 distinct alleles identified in the study was determined.